The Impact of E-WOM, Accessibility, and Attractiveness on Revisit Intention to Wediombo Beach Yogyakarta: The Mediating Role of Tourist Experience - Muhammad Thoyib Amali; Immanuel Dwi Asmoro Tunggal; Alfiatu Rohima (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
The aim of this research is to examine the influence of electronic word-of-mouth, accessibility, and attractiveness on the intention to revisit Wediombo Beach, as influenced by the tourist experience. This research uses an explanatory quantitative approach with data collected from a survey of 120 respondents who have visited Wediombo Beach. Path analysis, utilizing the SmartPLS program and the Sobel test to measure mediation variables, serves as the analysis technique. Hypothesis testing reveals that electronic word of mouth and attractiveness have a positive and significant influence on revisit intention, with the tourist experience acting as a mediator. The tourist experience also mediates the significant impact of accessibility, despite its negative value, on revisit intention. In regulating the impact of electronic word of mouth, accessibility, and attractiveness on revisit intention, the tourist experience serves as a partial mediating factor. Furthermore, researchers can suggest managerial implications for the Special Region of Yogyakarta Tourism Office and related tourism managers to improve the accessibility factor, which can start with making clear directions and improving the road quality to Wediombo Beach.